http://www.aulamedica.es/fh/pdf/10518.pdf - Marta García-Queiruga; Laura María Martínez-López; María Isabel Martín-Herranz; Teresa Seoane-Pillado; Elena Fernández-Gabriel; Teresa Calleja-Chuclá (Elsevier, 2016)
Objective: To assess the level of adherence to treatment with imatinib in patients with chronic myeloid leukaemia and its association with therapeutic response. Materials and methods: Study conducted on October, 2013 - March, 2014, including patients diagnosed with Chronic Myeloid Leukaemia on treatment with imatinib in the hospital. Therapeutic adherence was assessed through the standard Morisky-Green Questionnaire and the medication dispensing record. Those patients who did not complete 6 months of treatment and/or did not complete the questionnaire were excluded. Therapeutic response was assessed following clinical guidelines. The descriptive analysis of variables and correlation was conducted through Pearsons's Chi-Square Test. Results: The study included 31 patients. When assessing the level of association between response variables and therapeutic adherence: 1. The highest molecular response was reached by 68.4% of those patients with high adherence, and by 75% of those patients with intermediate adherence. 2. Complete molecular response was achieved by 57.9% of patients with high adherence, and by 58.3% of patients with intermediate adherence. No statistically significant differences were found in response variables between patients with high and intermediate therapeutic adherence. No association was observed between level of adherence and therapeutic response. Conclusions: We cannot confirm that a different level of therapeutic adherence might have an impact on response to imatinib, though this should be taken into account in cases of therapeutic failure or sub-optimal response